Caracterização de antenas planares com substrato metamaterial - Sousa Neto, Marinaldo Pinheiro de (2011)
This work presents a theoretical and numerical analysis for the radiation characteristics of rectangular microstrip antenna using metamaterial substrate. The full wave analysis is performed in the Fourier transform domain through the application of the Transverse Transmission Line - TTL method. A study on metamaterial theory was conducted to obtain the constructive parameters, which were characterized through permittivity and permeability tensors to arrive at a set of electromagnetic equations. The general equations for the electromagnetic fields of the antenna are developed using the Transverse Transmission Line - TTL method. Imposing the boundary conditions, the dyadic Green s function components are obtained relating the surface current density components at the plane of the patch to the electric field tangential components. Then, Galerkin s method is used to obtain a system of matrix equations, whose solution gives the antenna resonant frequency. From this modeling, it is possible to obtain numerical results for the resonant frequency and return loss for different configurations and substrates